Coupling between respiratory and sympathetic activities as a novel mechanism underpinning neurogenic hypertension - Machado, Benedito Honório; Zoccal, Daniel Breseghello [UNESP] (Springer Nature, 2011)
Enhanced sympathetic outflow to the heart and resistance vessels greatly contributes to the onset and maintenance of neurogenic hypertension. There is a consensus that the development of hypertension (clinical and experimental) is associated with an impairment of sympathetic reflex control by arterial baroreceptors. More recently, chronic peripheral chemoreflex activation, as observed in obstructive sleep apnea, has been proposed as another important risk factor for hypertension. In this review, we present and discuss recent experimental evidence showing that changes in the respiratory pattern, elicited by chronic intermittent hypoxia, play a key role in increasing sympathetic activity and arterial pressure in rats. This concept parallels results observed in other models of neurogenic hypertension, such as spontaneously hypertensive rats and rats with angiotensin II–salt-induced hypertension, pointing out alterations in the central coupling of respiratory and sympathetic activities as a novel mechanism underlying the development of neurogenic hypertension.
Keywords: Hypertension; Sympathetic overactivity; Respiration; Respiratory-sympathetic coupling; Hypoxia